Evaluation of mental and sleeping disorders in dental surgeons working in Altamira-PA during the COVID-19 pandemic period (Research, Society and Development, 2022)
The aim of this study was to evaluate the presence and level of mental and sleep disorders in dentists in the city of Altamira-Pará during the COVID-19 pandemic period. The analysis of this theme is justified by the importance of verifying the mental health of these professionals who, even not acting on the front line, had an impact on their professional performance. This research has a cross-sectional and quantitative character and was conducted through the application of an online questionnaire that assessed the profile of dental surgeons regarding professional practice during the COVID-19 pandemic period, the Anxiety Indication through the GAD Scale-7 (Generalized Anxiety Disorder 7), the sleep pattern through the Insomnia Severity Indication (ISI), the analysis of depression through the Patient Health Questionnaire (PHQ-9) and, finally, the level of stress by the Perceived Stress Scale (PSS-10). The study had the participation of 43 individuals. The results show relevant rates of insomnia, anxiety and depression, the latter being the main disorder related to the perception of high impact that the pandemic caused in the work routine. We emphasize that the participants relate the effects of the pandemic with the number of appointments provided. Therefore, it is necessary to analyze mental and sleep disorders in health professionals, including dentistry ones, and from this, elaborate strategies that act to prevent and control the disorders that these health professionals may develop, thus maintaining their mental health.